Enhancement of complement-dependent cytotoxicity by linking factor-H derived short consensus repeats 19-20 to CD20 antibodies - Prantl, Lena; Heider, Philipp; Bergmeister, Lisa; Calana, Katharina; Bohn, Jan-Paul; Wolf, Dominik; Banki, Zoltan; Bosch, Andreas; Plach, Maximilian; Huber, Georg; Schrödel, Silke; Thirion, Christian; et al. (Frontiers in Immunology, 2024)
Antibody-mediated complement-dependent cytotoxicity (CDC) on malignant cells is regulated by several complement control proteins, including the inhibitory complement factor H (fH). fH consists of 20 short consensus repeat elements (SCRs) with specific functional domains. Previous research revealed that the fH-derived SCRs 19-20 (SCR1920) can displace full-length fH on the surface of chronic lymphocytic leukemia (CLL) cells, which sensitizes CLL cells for e.g. CD20-targeting therapeutic monoclonal antibody (mAb) induced CDC. Therefore, we constructed lentiviral vectors for the generation of cell lines that stably produce mAb-SCR-fusion variants starting from the clinically approved parental mAbs rituximab, obinutuzumab and ofatumumab, respectively. Flow-cytometry revealed that the modification of the mAbs by the SCRs does not impair the binding to CD20. Increased in vitro lysis potency compared to their parental mAbs was corroborated by showing specific and dose dependent target cell elimination by CDC when compared to their parental mAbs. Lysis of CLL cells was not affected by the depletion of NK cells, suggesting that antibody-dependent cellular cytotoxicity plays a minor role in this context. Overall, this study emphasizes the crucial role of CDC in the elimination of CLL cells by mAbs and introduces a novel approach for enhancing CDC by directly fusing fH SCR1920 with mAbs.